2024
DOI: 10.1021/acs.inorgchem.4c01516
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Heterogeneous Engineering with the Vacancy Defect of Porous CoPv-MoxPv Nanosheets for an Accelerated Hydrogen Evolution Reaction

Long Qian,
Yao Zhu,
Huiting Hu
et al.

Abstract: Electrochemical water splitting is a possible way of realizing sustainable and clean hydrogen production but is challenging, because a highly active and durable electrocatalyst is essential. In this work, we integrated heterogeneous engineering and vacancy defect strategies to design and fabricate a heterostructure electrocatalyst (CoP v -Mo x P v /CNT) with abundant phosphorus vacancies attached to carbon nanotubes (CNTs). The vacancy defects enabled the optimization of the electronic structure; thereby, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(85 reference statements)
0
0
0
Order By: Relevance
“…On the other hand, vacancy defects have also been proven to be an effective method for altering interfacial chemical properties and exposing active sites. , Qian et al combined heterostructure engineering and vacancy strategies to fabricate a CoP v -Mo x P v /CNT electrocatalyst enriched with P defects and indicated that P vacancies can promote reaction kinetics and generate more active sites, ultimately displaying an overpotential of only 138 mV at 10 mA cm –2 for HER in 0.5 M H 2 SO 4 . Li et al reported NiSe 2 /Co 3 Se 4 -CNTs with rich Se vacancies and found that the generation of Se vacancies enhances the material’s adsorption capacity for OH – and increases the density of states (DOS) at the Fermi level, thereby improving the conductivity and enabling rapid interfacial electron transfer .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, vacancy defects have also been proven to be an effective method for altering interfacial chemical properties and exposing active sites. , Qian et al combined heterostructure engineering and vacancy strategies to fabricate a CoP v -Mo x P v /CNT electrocatalyst enriched with P defects and indicated that P vacancies can promote reaction kinetics and generate more active sites, ultimately displaying an overpotential of only 138 mV at 10 mA cm –2 for HER in 0.5 M H 2 SO 4 . Li et al reported NiSe 2 /Co 3 Se 4 -CNTs with rich Se vacancies and found that the generation of Se vacancies enhances the material’s adsorption capacity for OH – and increases the density of states (DOS) at the Fermi level, thereby improving the conductivity and enabling rapid interfacial electron transfer .…”
Section: Introductionmentioning
confidence: 99%